2019
DOI: 10.1016/j.chemosphere.2018.12.093
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk associated with the management of phosphorus in freshwaters using lanthanum and aluminium

Abstract: Human health risk associated with the management of phosphorus in freshwaters using lanthanum and aluminium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 141 publications
(162 reference statements)
0
26
0
1
Order By: Relevance
“…According to ATSDR (U.S. Toxic Substance Disorders Registrar General), a small amount of Al accumulated in organ tissues including the bones, brains, and kidneys over a long period of time may damage the human body (Exley 2013; D’Haese et al 2018). The German Federal Hazard Assessment (BFR) also warns people of eating habits, as daily exposure to Al is more dangerous to children than they are to adults (Nayak 2002; Shrivastava et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…According to ATSDR (U.S. Toxic Substance Disorders Registrar General), a small amount of Al accumulated in organ tissues including the bones, brains, and kidneys over a long period of time may damage the human body (Exley 2013; D’Haese et al 2018). The German Federal Hazard Assessment (BFR) also warns people of eating habits, as daily exposure to Al is more dangerous to children than they are to adults (Nayak 2002; Shrivastava et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the use of aluminium salts as a flocculants to purify drinking water has long been criticised [3]. The relationship between aluminium exposure and Alzheimer's disease has been the focus of intense research, and epidemiological investigations have found a strong correlation between the accumulation of aluminium in the brain and Alzheimer's disease, both for workers occupationally exposed to aluminium and for people who drink tap water that might contain higher aluminium content after being purified with aluminium salts [4,5]. With regard to drinking water exposure, an important question is whether the aluminium is derived from natural sources for instance from ingestion of clay minerals or as a consequence of water treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to drinking water exposure, an important question is whether the aluminium is derived from natural sources for instance from ingestion of clay minerals or as a consequence of water treatment methods. Water treatment using aluminium sulphate (VI) generally increases the percentage of dissolved, low molecular weight, polyaluminium species that are chemically reactive and possibly more readily absorbed [4]. Aluminium has been found in the brain of Alzheimer's patients in the amyloid deposits characteristic of this disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolyzing metal ions, for instance ferric ions, have been employed as coagulants for treatment of swine wastewater since they are highly effective in removing suspended colloids and particles (Laridi, Auclair, & Benmoussa, 2005). Comparing to the aluminum (electro) coagulation, ferric (electro)coagulation has advantages for fewer metal residues and less potential risk (D'Haese et al, 2019). Ferric electrocoagulation has been found to effectively remove turbidity and COD of swine wastewater (Mores et al, 2016), and it could also remove sulfide or arsenic compounds in the synthetic water at an optimized condition (Ali, Khan, & Asim, 2011;Wang, Lin, & Hu, 2019).…”
Section: Introductionmentioning
confidence: 99%